The Statue of a Doctor Who Experimented on Enslaved Women still Stands in Alabama. But now There’s also a Monument to His Victims. - Matchan, Linda (Washington Post, 2021)
Michelle Browder’s “The Mothers of Gynecology” remembers Black women who endured surgeries without anesthesia, or consent.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice noir.e; _Nettoyé

Artistes afro-brésiliennes, d’un siècle à l’autre - Giunta, Andrea (AWARE : Archives of Women Artists, Research and Exhibitions, 2021)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Memorias americoafricanas en el trabajo de artistas brasileñas contemporáneas - Sardelich, Maria Emilia; Cao, Marian López Fernandez (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
La memoria hace referencia a un conjunto de funciones psíquicas que permiten la actualización de imágenes de hechos pasados o que se representan como pasados. A diferencia de los estudios históricos, los de la memoria resaltan las subjetividades, amplían la discusión más allá del recuerdo y el olvido, y desplazan el debate hacia quien tiene el derecho a narrar su historia y aquellos que en ella se encuentran. Las inquietudes en torno a la memoria y sus lugares también se hacen visibles en el inquieto horizonte artístico, en el que pasados recientes y distantes se articulan en registros sobre diversas formas de traumas. Este artículo propone una reflexión sobre las relaciones entre arte y memoria a partir de la producción de dos artistas brasileñas contemporáneas: Rosana Paulino (São Paulo, 1968) y Aline Motta (Niterói, 1974). El análisis de esa producción se fundamenta en la interdisciplinaridad de los estudios de la memoria y destaca cómo la creación artística ofrece una posibilidad de resignificación individual y colectiva. Asimismo, conceptúa memorias americoafricanas como aquellas que emergen no solo en la memoria individual de las artistas presentadas en este artículo, sino también en la de muchas otras mujeres que se identifican con Americoáfrica como un sistema etnogeográfico de referencia. Son memorias americoafricanas porque se han gestado en la resistencia y creatividad contra la opresión, la humillación y la deshumanización, y que se insurgen contra la historia única proponiendo una revisión de la historiografía del país y del arte producido a partir de esos lugares. Memory refers to a set of psychic functions that allow the updating of images of past events or events that are represented as past. Unlike historical studies, memory studies highlight subjectivities, expand the discussion beyond memory and oblivion, and shift the debate towards who has the right to narrate their history and those who are in it. The concerns about memory and its places also become visible in the restless artistic horizon, in which recent and distant pasts are articulated in registers about various forms of trauma. This paper proposes a reflection on the relationship between art and memory based on the production of two contemporary Brazilian artists: Rosana Paulino (São Paulo, 1968) and Aline Motta (Niterói, 1974). The analysis of this production is based on the interdisciplinary nature of memory studies and highlights how artistic creation offers a possibility of individual and collective resignification. Likewise, it conceptualizes African-American memories as those that emerge not only in the individual memory of the artists presented in this article, but also in that of many other women who identify with Africa-America, as a reference ethnogeographic system. They are African-American memories because they have been born in resistance and creativity against oppression, humiliation and dehumanization, and because they insurrect against the unique history, proposing a review of the historiography of the country and the art produced out of those places.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice noir.e; _Nettoyé

Only Skin Deep: Changing Visions of the American Self - Fusco, Coco; Wallis, Brian (Abrams and International Center of Photography, 2003)
"By bringing together a provocative selection of essays and images, Only Skin Deep: Changing Visions of the American Self addresses the issues of nation, race, and selfhood and how they are depicted in ways that are challenging and informative, prompting readers to consider the impact of photography on our everyday lives." "If photographs are chiefly responsible for perpetuating myths of American identity, can a different reading of these representations break down distorting stereotypes? This is the central question posed by Only Skin Deep. The authors in this book forcefully argue that race and nation - and, indeed, photography itself - are fictions, cultural constructions that shape our social interactions. Even as symbols, these photographic depictions of ethnic difference and cultural superiority have very real consequences. This collection of works and essays addresses, for example, the lingering consequences of American colonial expansion; the conflict between public and private visualizations of individuals; the role of commercial imagery in shaping gender roles; the impact of fantasy in ethnic or ethnographic photography; and the uses of science to provide justification for politicized depictions of "race."" "Accompanying a major exhibition of the same name, Only Skin Deep offers a critical rereading of the archive of the history of photography. This applies to the works of famous photographers - such as Dorothea Lange, Walker Evans, Ansel Adams, and Edward Steichen - as well as lesser-known historical figures, including Charles Eisenmann, Frances Benjamin Johnston, Will Soule, and Toyo Miyatake. A substantial part of the book is devoted to contemporary artists and photographers who have moved beyond the multicultural approach to representations of "race" and have made an investigation of the semiotics of cultural identity a prevalent theme over the past decade. Among the recent photographers included are: Nancy Burson, Nikki S. Lee, Glenn Ligon, Paul Pfeiffer, Hulleah Tsinhnahjinnie, Cindy Sherman, Lorna Simpson, and Andres Serrano."–(BOOK JACKET)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé